2005
DOI: 10.1111/j.1365-2036.2005.02562.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin suppresses bacterial overgrowth, increases fasting insulin but does not correct low acylated ghrelin concentration in non‐alcoholic steatohepatitis

Abstract: SUMMARYBackground: Insulin resistance and oxidative stress induced by products of small intestinal bacterial activity are putative factors in the pathogenesis of non-alcoholic steatohepatitis. Acylated ghrelin is the biologically active form of an orexigenic gastric hormone that modifies insulin sensitivity and body composition. Aim: To investigate the effect of ciprofloxacin on small intestinal bacterial activity, ethanol, ghrelin and insulin in non-alcoholic steatohepatitis patients. Methods: Twelve non-alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 62 publications
5
43
2
1
Order By: Relevance
“…They found that 50% of NASH patients had a positive breath test in comparison with only 22% of their healthy controls. In other studies, the occurrence of SIBO in NAFLD/NASH has been documented using either the lactulose [10] or glucose breath test [73]. Recently, the presence of SIBO has been associated with the severity of liver steatosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…They found that 50% of NASH patients had a positive breath test in comparison with only 22% of their healthy controls. In other studies, the occurrence of SIBO in NAFLD/NASH has been documented using either the lactulose [10] or glucose breath test [73]. Recently, the presence of SIBO has been associated with the severity of liver steatosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of fatty degeneration have been reported in morbidly obese patients with jejuno-ileal bypass [8,9] and in small bowel diverticulosis [10], both conditions favouring bacterial overgrowth. Wigg et al [11] and Sajjad et al [12] showed that the prevalence of SIBO assessed by (14) C-D-xylose and lactulose or glucose breath tests was higher in patients with NASH compared with control subjects. However, in patients with morbid obesity, the prevalence of SIBO is unknown and its role in liver injuries has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, low ghrelin serum levels were found in NAFLD patients [137] while in another study it was demonstrated that low ghrelin levels could not be attributed to small intestinal bacterial activity [139], which is encountered commonly in non-alcoholic steatohepatitis. In addition, ghrelin levels were significantly correlated with Homeostasis Model Assessment index (HOMA-IR ) in both healthy and NAFLD patients [137].…”
Section: Ghrelin and Livermentioning
confidence: 98%